Hypoxic Ischemic Encephalopathy in Forensic Medicine - Yıldız Silahlı, Nicel; Celkan, Tiraje (The Bulletin of Legal Medicine, 2021)
Neonatal encephalopathy is a clinical picture with convulsion, respiratory depression and hypotonia "appeared" in babies born at 35 weeks and after the first month. The clinical picture detected in the cases varies. When Hypoxic Ischemic Encephalopathy (HIE) is suspected clinically, all causes should be evaluated except for reasons belonging to the mother, the placenta or the child. Many cases that cause medico-legal problems have been reported between the parents and the parents who are in a healthy baby's care and the physicians attending their birth. After determining that a significant part of the forensic medical files is the HIE that obstetrics and neonatal physicians are accused together or individually, we aimed to draw attention to this issue and to reveal the reasons for the malfunctions and errors, if any. Meanwhile, we aimed to develop an algorithm that physicians who evaluate HIE in forensic medicine can use while examining the file and provide the same language and perspective.
Keywords: Hypoxic Ischemic Encephalopathy; Forensic Medical Approach